Linearization - Advantages And Shortcomings Toward Control System Design - Kamarudin, Muhammad Nizam; Md Rozali, Sahazati; Hairi, Mohd Hendra; Khamis, Alias; Husain, Abdul Rashid (Penerbit Universiti Teknikal Malaysia Melaka, 2019)
This brief manuscript discusses the necessity to linearize nonlinear systems. Thorough review on nonlinear phenomena in dynamical and numerical system is presented. The methodology to linearize nonlinear system in Jacobian approach is shown in didactic manner. Numerical and dynamical example of nonlinear system is provided to enhance understanding. Afterward, the comparison between both linearized and non-linearized system is literally discussed. The outcomes concluded that linearization process is a linear approximation of a nonlinear system that is only valid in a small region around an operating point.